Isolasi, Karakterisasi, dan Identifikasi Bakteri Endofit Sargassum polycystum Penghasil Enzim Alginat Lyase - Yesica Bella Safitri; Agus Setiawan; Ni Luh Gede Ratna Juliasih; Endang Linirin Widiasuti; Gregorius Nugroho Susanto (Universitas Bangka Belitung, 2023)
Alginate, polysaccharide from marine brown algae, is widely used for antitumor, anti-inflammatory, and also antiviral. However, alginate has large molecular weight that difficult to digest in some organsims. Therefore, it is important to look for the alginate lyase enzyme to break down the alginate. The purpose of this study was to obtain bacterial isolates that produce alginate lyase enzymes from Sargassum polycystum. Isolation of alginate lyase-producing bacteria was carried out by collecting Sargassum polycystum. from Sebalang Beach, Tarahan, South Lampung then the bacteria were isolated by the dilution method. The colonies obtained were purified and selected using qualitative (clear zone) and semi-quantitative activity tests, and identified morphologically, biochemically and molecularly using the 16S-rDNA gene. In this study, 20 pure bacterial isolates were obtained with one isolate having alginate lyase activity, namely PTF and PTH. The results of biochemical tests and molecular characterization showed that the isolate was Bacillus cereus.